2010
DOI: 10.1249/jsr.0b013e3181de7ec5
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Running Injuries

Abstract: Evidence for preventive strategies to lessen running injuries is needed as these occur in 40%-50% of runners on an annual basis. Many factors influence running injuries, but strong evidence for prevention only exists for training modification primarily by reducing weekly mileage. Two anatomical factors - cavus feet and leg length inequality - demonstrate a link to injury. Weak evidence suggests that orthotics may lessen risk of stress fracture, but no clear evidence proves they will reduce the risk of those at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(143 citation statements)
references
References 23 publications
6
125
0
5
Order By: Relevance
“…Furthermore, the additional mileage did not appear to increase ABT in Police Force Recruits 3 aerobic fitness to a greater degree (34). These findings have been reproduced in several other studies, which have found that the potential for injury increases disproportionally with increasing running mileage, once a certain threshold is reached, with little additional fitness benefit (8,12,31).…”
Section: Introductionsupporting
confidence: 55%
“…Furthermore, the additional mileage did not appear to increase ABT in Police Force Recruits 3 aerobic fitness to a greater degree (34). These findings have been reproduced in several other studies, which have found that the potential for injury increases disproportionally with increasing running mileage, once a certain threshold is reached, with little additional fitness benefit (8,12,31).…”
Section: Introductionsupporting
confidence: 55%
“…With such a large number of people running, the risk and incidence of running-related injuries will likely continue. During a 12-month period of running, it has been reported that up to 90% of runners will suffer a running-related injury (Fields, Sykes, Walker, & Jackson, 2010;Satterthwaite, Larmer, Gardiner, & Norton, 1996;Van Gent, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Ainda que inferiores aos dados de Daoud et al 6 que informada presença deste tipo de apoio em 59% dos corredores. Alguns estudos 5 assinalam que os atletas universitários que possuem apoio atrasado apresentam o dobro de lesões por esforço repetitivo em comparação aos que se apoiam no metatarso.…”
Section: Discussionunclassified
“…Deste modo, apesar da alta tecnologia aplicada aos tênis esportivos para corredores, eles continuam sofrendo ferimentos. Neste sentido, Fields et al 5 enfatizam que nas carreiras de corredores de resistência a taxa de lesões se mantém relativamente constante. Durante os úl-timos 30 anos, tanto os corredores daquela época quanto os atuais, continuam apresentando lesões.…”
Section: Correspondênciaunclassified